En roll som etolog i det svenska samhället : första steget till certifiering av etologer - Lotfollahi, Tara (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
Ethology is a relatively young science, since the first studies of animal behaviour was done by Charles Darwin. The definition of the term ethology has been discussed over the years, however present scientists agree on the interpretation “animal behaviour and the causes behind them”. Even though a big part of the Swedish society depends on animals, for instance within meat and dairy production, as pets, zoos, laboratory animals and game management, it seems like the term ethology and ethologist as a professional role is not well known. The aim of this paper is to investigate the need of ethologists in today’s society in two different areas, and also what the possibilities are to certify ethologists. A questionaire was made and used for understanding what knowledge Swedish pet-owners have of ethology and ethologists, how pet-owners finds knowledge about their pets and to understand if there is a need of ethologists in this context or not. A study of current research was made to conclude whether ethologists are needed as co-workers with veterinarians towards a better animal welfare. Also politicians, a federation of labor union and an interest organization was contacted to take the first step of certifying Swedish ethologists. The results showed that ethologists actually are needed to help spreading knowledge about animal behaviour and welfare, to maintain the Swedish animal welfare and to work in collaboration with veterinarians. It also showed that ethologists as a professional role is not well known yet, but if a certification is successful that would presumably change and have a great impact on the animal welfare in Sweden.